Long read Nanopore sequencing identifies precise breakpoints of a de novo paracentric inversion that disrupt the MEIS2 gene in a Chinese girl with syndromic developmental delay - Jianxin Tan; Mingtao Huang; Xiuqing Ji; An Liu; Fengchang Qiao; Cuiping Zhang; Lulu Meng; Yan Wang; Zhengfeng Xu; Ping Hu (BMC Pediatrics)
Abstract Background Chromosomal inversions are underappreciated causes of rare diseases given their detection, resolution, and clinical interpretation remain challenging. Heterozygous mutations in the MEIS2 gene cause an autosomal dominant syndrome characterized by intellectual disability, cleft palate, congenital heart defect, and facial dysmorphism at variable severity and penetrance. Case presentation Herein, we report a Chinese girl with intellectual disability, developmental delay, and congenital heart defect, in whom G-banded karyotype analysis identified a de novo paracentric inversion 46,XX, inv(15)(q15q26.1) and other conventional approaches including chromosomal microarray analysis and whole exome sequencing were failed to detect any pathologic variants that can explain the phenotypes of the proband. Subsequently, long-read Nanopore sequencing was directly conducted and defined the breakpoint position of the inversion, disrupting the MEIS2 gene at intron 8. These breakpoints were also confirmed by Sanger sequencing. Conclusions In conclusion, we report the first chromosomal inversion disrupting the MEIS2 gene, which was fine-mapped by long read Nanopore sequencing. Our data not only expand the clinical spectrum of MEIS2-caused syndromic developmental delay, but also illustrate the value of long-read sequencing in elucidating the precise genetic etiology of patients with relatively nonspecific clinical findings and chromosomal inversion that are beyond the resolution of conventional approaches.